THE BEST WAY FOR TEACHING SPEAKING AT SENIOR HIGH SCHOOL - I Gusti Nyoman Putra Kamayana (Seminar Ilmiah Nasional Teknologi, Sains, dan Sosial Humaniora (SINTESA), 2018)
ABSTRACTTeaching students strategies for answering the questions is a part of speaking. The failure of students in speaking are caused of misunderstanding the questions and how it relates to the answer. It is valuable skill for all students to obtain , especially struggling speakers. The best way teaching speaking assists students in relating prior knowledge to the topic of speaking . It is becomes a conscious process students actively engage in when speaking about the topic, especially difficult speaking in answering the question. With this strategy, students become aware of the relationships between questions and answers. The students will begin to understand where the answers come from and thus are better able to answer the questions correctly. This paper reveals an alternatively model for the best way teaching speaking. Hopefully, it will be useful for English teacher who are training students to speak and face the implementation of Curriculum 2013 at senior high school.Keywords: Question and answer relationship, speaking strategy